THE EFFECT OF SINGLE HIGH-VELOCITY, LOW-AMPLITUDE SPINE MANIPULATION ON POSTURE, FUNCTIONAL STATE OF TORSO, THIGH MUSCLES, AND VERTICAL JUMP HEIGHT - Ozols, Edgars; Galeja, Zinta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The effects impact of single high-velocity, low-amplitude (HVLA) spinal manipulation on posture, torso, and thigh functional condition, and the height of the vertical jump have not been adequately studied. The research aims to investigate the immediate changes caused by a single spinal vertebral HVLA manipulation 3 weeks after posture, torso, and thigh muscle functional state, and vertical jump height. The study involved 46 men aged 18-25 years old who practiced indoor volleyball training at least twice a week, as well as a deviation of the vertebral vertebrae from the non-thymic position. Initially, posture was assessed using the photogrammetry method and muscle length was assessed using the goniometry method. A vertical jump height test was performed by the Sargent Jump test. A single HVLA spinal manipulation was performed by a certified chiropractor for segment correction. Then, a re-assessment of posture (photogrammetry), re-assessment of movement volume (goniometry) as well a re-assessment of vertical jump height test- the Sargent Jump test was performed. After 3 weeks post HVLA manipulation participants were retested. The main findings are: immediately after the HVLA spinal correction changes in posture were observed in all evaluated parameters, deviations from the norm decreased by 25.45% ± 1.27% (p < .005), while the vertical jump height test results immediately after HVLA increased by 4.34% ± 0.11% (p < .005). After 3 weeks post HVLA spine manipulation therapeutic effect was reduced by 5.48% ± 1.27% (p < .005), while the Sargent Jump test result 3 weeks after manipulation decreased by 0.05% ± 0.11% (p > .005). Conclusion: the persistence of the effect of a single HVLA spine manipulation was maintained for 3 weeks after the manipulation into the posture.